Photo-assisted effective and selective reduction of CO2 to methanol on a Cu–ZnO–ZrO2 catalyst. (27th October 2022) - Wang, Jian; Qu, Xiuli; Djitcheu, Xavier; Meng, Qingrun; Ni, Zenan; Liu, Huimin; Zhang, Qijian
Abstract : Highly selective catalysis of CO2 hydrogenation to methanol with photo-assistance on Cu–ZnO–ZrO2, a photothermal synergistic catalyst. Abstract : The emergence of the "double carbon" era indicates more significant concerns in CO2 utilization. CO2 to methanol conversion is one of the most promising methods for converting CO2, but its extensive application is restricted by harsh reaction conditions. A photo-assisted reaction is expected to effectively alleviate the harsh reaction conditions and exhibits high catalytic activity. In this work, the contribution of photo-assistance was investigated in the CO2 reduction reaction over Cu–ZnO and Cu–ZnO–ZrO2 catalysts. Cu–ZnO–ZrO2 exhibits higher methanol selectivity (61.2%) than Cu–ZnO (34.2%), and methanol selectivity is further improved from 61.2% to 70.4% with the photo-assisted reaction. The superior performance of the Cu–ZnO–ZrO2 catalyst is due to the generation of more oxygen vacancies (Ov ) on the ZnO surface, which reduce the bandgap of the catalyst and change the conduction band (CB) position. The generation of electrons is promoted under light irradiation, making the catalyst more favorable for the reduction of CO2 to methanol. Therefore, the effective reduction of CO2 to methanol is feasible on the photo-assisted Cu–ZnO–ZrO2 catalyst.